The genesis of political parties (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In this article, we have analyzed the role and place of political parties in the political system of the state. The basic characteristics of political parties are considered. An attempt has also been made to analyze methodological approaches to the study of political parties by individual political scientists and sociologists. Some connections of political parties by ideology, by the principle of purpose and harmony of political parties as a political force influencing political processes in the world are outlined. The author of this article considers a political party as a political institution that plays an important role in the life of the state and society.
Keywords: political party, state, society, political system, ideology,government,purpose, political principles